Licensing and publichouse reform in Ireland - Lawson, William (Statistical and Social Inquiry Society of Ireland, 1906)
"No apology is, I think, needed for introducing this subject to the consideration of the Society, although I could wish that the task had fallen to one more conversant with it than I am. The evils of intemperance are so great that it is no wonder that efforts have been made from time to time to check it by individuals, by societies established for the purpose, by Bishops and clergy of all denominations, and by legislation, actual or attempted. In the present year attention has been particularly called to the subject by the protest issued by the Irish Roman Catholic Bishops, by pastorals of members of that body, and by legislative measures introduced in Parliament by the Government, and by private members.
Read Friday, Feb. 28th, 1902
Keywords: Alcohol consumption; Public houses; 314.15